Development of an advanced control algorithm for DAB DC/DC converters: inrush current limitation and enhanced operation in transient states - Bachman, Serafin; Turzyński, Marek (Bulletin of the Polish Academy of Sciences Technical Sciences, 2024)
The publication addresses the dynamic state challenges encountered during development of a dual active bridge (DAB) converter within DC microgrid systems. The conventional startup method is identified as instigating a cascade of unfavorable outcomes, encompassing elevated starting current, transformer current asymmetry, DC voltage distortions, EMI and heightened thermal stress on semiconductor components. Additionally, it necessitates precise calibration of magnetic components and diodes. A proposed remedy to these issues is introduced, involving a control method based on an additional phase shift to modulate the current of the primary H bridge. This novel control methodology is posited as a means to mitigate the aforementioned undesirable effects associated with traditional converter initiation techniques. The research also delves into considerations of a proper design procedure for the converter. Emphasis is placed on integrating the novel control methodology into the design framework in order to effectively address challenges arising during transient states. Validation of the proposed solution is substantiated through a series of laboratory tests, the results of which are comprehensively presented in the article. These tests affirm the efficiency of the system when incorporating the novel control methodology, thereby substantiating its practical utility in mitigating the issues identified during the initiation phase of the DAB converter in DC microgrid systems.